Penguatan Tata Kelola Keuangan Pada Jaringan Ekowisata Desa (JED) di Bali : Pengabdian - Anak Agung Gede Krisna Murti; Anak Agung Istri Krisna Gangga Dewi; Luh Diah Citra Resmi Cahyadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to strengthen financial governance within the Jaringan Ekowisata Desa (JED) in Bali, which has been facing challenges such as inconsistent manual bookkeeping, low financial literacy, and the absence of standard operating procedures (SOP). The program was implemented using a participatory approach that engaged JED management and village representatives throughout all stages of the activities, including problem identification, financial literacy training, SOP formulation, and the implementation of  digital bookkeeping system. The results indicate significant improvements in participants’ understanding of financial recording and reporting, the establishment of an agreed financial SOP, and the effective use of digital bookkeeping systems across all partner villages. This transformation has led to more transparent, accountable, and efficient financial governance while also increasing youth involvement in village financial management. The program recommends continued capacity building through mentoring, regular monitoring, and the development of more adaptive digital systems to ensure replication in other tourism villages across Indonesia.